(untitled) (Canadian Perspectives on Academic Integrity, 2021)
The pivot to remote teaching and learning in March 2020 as a result of COVID-19 presented numerous challenges for students, faculty, and administrators across higher education in Manitoba, in particular, those related to academic integrity and academic misconduct. Panelists with diverse roles in higher education share their experiences, lessons learned, and successes from the past year. This session highlights the importance of continued conversations, problem solving, and implementation of new solutions for fostering academic integrity, building communities with shared values and priorities, and improving policies and procedures.